2019
DOI: 10.1080/1331677x.2019.1636699
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of SMEs’ performance: evidence from European countries

Abstract: This article aims to examine how certain economic and social factors influence short-and long-term performance of small and medium enterprises (SMEs). SMEs' performance is defined by using the value added (VA) by SMEs, as a percent of the total VA by enterprises. The study targets European Union (EU) countries selected by the authors following a cluster analysis procedure. In order to obtain short-and long-term influences, an analysis that carries out three types of tests is conducted: testing stationarity, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 43 publications
(45 reference statements)
0
54
1
2
Order By: Relevance
“…In terms of the financial condition of family firms, their performance in times of uncertainty, economic downturn, crisis, or recession seems essential. The focal questions in this study are whether family businesses fare better under challenging times than non-family businesses and whether they retain stability and recover more quickly (Cicea et al 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of the financial condition of family firms, their performance in times of uncertainty, economic downturn, crisis, or recession seems essential. The focal questions in this study are whether family businesses fare better under challenging times than non-family businesses and whether they retain stability and recover more quickly (Cicea et al 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Görg et al (2000) presented empirical evidence into the determinants of start-up size, using data for manufacturing firms in Ireland and found that the determinants of start-up size for the Irish manufacturing firms differ in their importance for small and large-scale entrants. Cicea et al (2019) examined how certain economic and social factors influence short-and long-term performance of small and medium enterprises. The result suggested that in developed economies, in the short-run, factors such as the perceived level of corruption or the level of GDP influence on SMEs performance, indirect way, while in developing economies, SMEs' performance establishes a relationship in the short-run with factors having a more direct influence, factors such as the funds absorption rate or the unemployment.…”
Section: Finance Of Start-up Companiesmentioning
confidence: 99%
“…So there is a group of authors who strongly criticize the high level of net working capital [18,19]. It is worth trying to create optimal working capital management strategies for the company [20,21,22,24] In addition, a growing group of authors claims that a high level of net working capital not only reduces potential profits, but also raises the risk of companies functioning [25,26,27,28,29,30,31]. Therefore, in face of difficulty managers need to choose such a strategy of working capital management in order to obtain high profits, and at the same time not expose the company to loss of financial liquidity.…”
Section: Working Capital -Literature Reviewmentioning
confidence: 99%